2014
DOI: 10.1002/bjs.9390
|View full text |Cite
|
Sign up to set email alerts
|

Blue dye is sufficient for sentinel lymph node biopsy in breast cancer

Abstract: Blue dye performed well as a single modality for SLN biopsy. Non-identification, axillary nodal recurrence and serious allergic reactions were uncommon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…Simon first reported that MBD could serve as an alternative to isosulfan blue in combination with radioisotopes for SNB in breast cancer[ 17 ], and similar conclusions were drawn by other researchers[ 18 – 21 ]. Recently, several studies reported that blue dye alone was sufficient for identifying SNs in breast cancer [ 22 – 24 ]. Thus, the use of MBD alone as a mapping method for SNB seems feasible and may expand the use of SNB in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Simon first reported that MBD could serve as an alternative to isosulfan blue in combination with radioisotopes for SNB in breast cancer[ 17 ], and similar conclusions were drawn by other researchers[ 18 – 21 ]. Recently, several studies reported that blue dye alone was sufficient for identifying SNs in breast cancer [ 22 – 24 ]. Thus, the use of MBD alone as a mapping method for SNB seems feasible and may expand the use of SNB in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…If the MRI artefact due to residual magnetic tracer still poses a problem, SLNB can be performed using other tracers. (19)(20)(21) Patients requiring pre-operative MRI imaging, for instance patients undergoing primary chemotherapy, are eligible for localization using these magnetic markers but since the artefacts on MRI are large and will impact on the ability to report on response to treatment, the magnetic markers should be placed immediately prior to surgery, after completion of primary chemotherapy. It might also be possible to decrease the artefact, by making the magnetic markers thinner or by lowering the iron content of these magnetic markers.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] False-negative rates are low and a negative SLN is now accepted as being representative of node-negative disease. [13][14][15] The recent American College of Surgeons Oncology Group Z0011 trial has further shown that axillary lymph node dissection can be omitted in women with low-burden SLN disease who receive adjuvant whole breast irradiation and chemotherapy. 16 Since SLN biopsy involves only a limited dissection of the low level I axilla, potential complications of postoperative bleeding from a slipped clip or ligature, or oozing from the surgical bed and seroma formation is minimal, obliterating the need for surgical drains.…”
Section: Introductionmentioning
confidence: 99%